JUMLAH BINTIL AKAR DAN HASIL KACANG TANAH (Arachis hypogaea L.) KULTIVAR LOKAL ASAL PANDEGLANG PADA KONDISI KETERSEDIAAN AIR TANAH YANG MENURUN - Rusmana . (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACTThe objective of this experiment were find out responses various local peanut cultivars of Pandeglang to soil water availability decline condition. Randomized complete block design with three replications was used in this experiment. First factor is level of soil water availability consisted of three levels (100%, 75%, and 50%). Second factor is local cultivar of Pandeglang consisted of four levels(local cultivar of Menes, of Cibaliung, of Malingping, and of Cikeusik). Result of research indicates that decline soil water availability results degradation of number of root nodules and seed wight per plant for all local cultivar peanut of Pandeglang. Degradation of soil water availability out of 100% becomes 75%to result degradation of number of root nodules per plant average of 24,59% and degradation of soil water availability out of 100% becomes 50% to result degradation of number of root nodules 31,15%. Degradation of soil water availability out of 75% becomes 50% doesn't show degradation of number ofroot nodules manifestly. Degradation of soil water availability out of 100% becomes 75% to result degradation of seed wight average of 10,77% and degradation of soil water availability out of 100% becomes 50% to result degradation of seed wight 22,08%. Degradation of soil water availability out of75% becomes 50% doesn't show degradation of seed wight manifestly.Key words: local cultivar, peanut, root nodule, soil water availability